Penafsiran Ayat-Ayat Ibadah (Studi Pemikiran Tafsir Harun Nasution) - Anshori Anshori (Nun : Jurnal Studi Alquran dan Tafsir di Nusantara, 2020)
This article discuss about Harun Nasution’s thought in doctrine of Islam, particularly relate with his thought about observance verses in al-Qur’ān. He is one of the figure indonesian modernist because his effort to criticize understanding society that be judged taqlid or a reclusive gesture and closing the ijtihad doors. In his opinion, the advances of science in the time of classical Islam period were none other than due at that time the ijtihad doors were wide open. Therefore, the notion held by Harun Nasution is the rational theology as adopted by Muhammad Abduh who is also close to Mu’tazilah. Harun argued that in the doctrine of Islam, divided inti two doctrines, that are unchangeable teachings, and then adaptable teachings that could be changed. The unalterable doctrine is like the Qur’anic text that is the source of the doctrine of Islam. As for the interpretation or understanding of the Qur’anic text includes something that can be changed in which it’s understanding is tailored to the needs of the ages.